RESEPSI PEREMPUAN PEROKOK MENGENAI BAHAYA MEROKOK DALAM IKLAN LAYANAN MASYARAKAT “DON’T BREAK MY HEART” - Attila, Frida; Mulyana, Ahmad (Reputasi : Jurnal Public Relations, 2025)
Public service advertising as a creative production often carries an ideology that perpetuates gender-based discriminatory values. No exception is the phenomenon of female smokers in the public service advertisement “don't Break my Heart”. Public acceptance of advertising messages can show a form of rejection or resistance to the discourse brought. So did the women smokers who received the message. This study aims to uncover the reception of women smokers regarding the dangers of smoking in the public service advertisement “don't Break my Heart". This research uses Encoding-Decoding theory and audience reception analysis method. Researchers found 2 informants in the opposition position, 2 informants in the negotiating position and 1 informant in the dominant-hegemonic position. The position of the informant shows that the informant as an active audience is aware of the potentials in public service advertisements that make her as a female smoker increasingly repressed and stigmatized in negative labels.